Association of Diabetes Mellitus on Cardiac Remodeling, Quality of Life, and Clinical Outcomes in Heart Failure With Reduced and Preserved Ejection Fraction - Yap, J. (NLM (Medline), 2021)
10.1161/JAHA.119.013114